2017
DOI: 10.1017/s0950268817000929
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of invasive disease caused byNeisseria meningitidisserogroup Y in Sweden, 1995 to 2012

Abstract: SUMMARYOver the period 1995–2012, the incidence of invasive meningococcal disease (IMD) caused by Neisseria meningitidis serogroup Y (NmY) increased significantly in Sweden. This is mainly due to the emergence of a predominant cluster named strain type YI subtype 1, belonging to the ST-23 clonal complex (cc). The aim of this study was to examine the clinical picture of patients with invasive disease caused by NmY and to analyse whether the predominant cluster exhibits certain clinical characteristics that migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 21 publications
2
29
0
3
Order By: Relevance
“…Instead, our results suggest that point mutations in genes involved in host cell interactions have led to a change in adhesion to epithelial cells, which may have improved colonization, in turn increasing transmission and resulting in expansion of this sublineage. This is also supported by a study showing that no significant differences were found in mortality or clinical outcome between the Swedish strain YI sublineages 60 . It is therefore probable that sublineage 1 has lower virulence but higher transmissibility; this may be due to either the genetic differences found in the present study or an immunologically-naïve host population.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Instead, our results suggest that point mutations in genes involved in host cell interactions have led to a change in adhesion to epithelial cells, which may have improved colonization, in turn increasing transmission and resulting in expansion of this sublineage. This is also supported by a study showing that no significant differences were found in mortality or clinical outcome between the Swedish strain YI sublineages 60 . It is therefore probable that sublineage 1 has lower virulence but higher transmissibility; this may be due to either the genetic differences found in the present study or an immunologically-naïve host population.…”
Section: Discussionsupporting
confidence: 63%
“…These gene products are involved in adhesion, iron acquisition, bacterial immune system, endotoxin production, and mobile elements, and have been associated with meningococcal hyperinvasive lineages 38,[51][52][53][54][55][56] . Their absence could therefore explain the particular clinical outcomes such as pneumonia commonly associated with serogroup Y disease [57][58][59][60] . Furthermore, CRISPR-associated genes cas1 and cas2, which were found among all cc23 genomes, have previously been shown to be associated with carriage isolates 53 .…”
Section: Discussionmentioning
confidence: 99%
“…These isolates were frequently of serogroup Y (Supplementary Table). Indeed, IMD due to serogroup Y is frequently observed in elderly and associated with u and respiratory manifestations such as bacteremic pneumonia (4,12). Secondary invasive meningococcal infections were reported to occur 7 to 10 days after u infections (4, 6).…”
Section: Main Textmentioning
confidence: 99%
“…IMD cases due to NmY cc23 have been increasing in France and in other European countries since 2010 (6). NmY (of cc23 and other cc) are frequently observed in the elderly and are involved in pneumonia (7). However, many NmY/cc23 cases are now occurring in adolescents and young adults who have a higher prevalence of meningococcal carriage (8), thereby perhaps providing an opportunity for concurrently carried bacterial species to exchange genetic material (Fig.…”
mentioning
confidence: 99%